Today's heroes: The print media discourse on accomplished athletes - Sæmundsson, Guðmundur; Jóhannesson, Ingólfur Ásgeir (School of Social Sciences, 2023)
Sports constitute the main interest of a significant percentage of the Icelandic nation, when assessed on the basis of media coverage. In spite of the nation´s small population, Icelandic athletes have been successful at major sports events abroad and have even brought medals and trophies home. The article deals with the conclusions of an analysis of printed media coverage relating to elite Icelandic athletes. The aim of the analysis is to discover which elements are shared in this coverage, how it has developed in the print media and whether it varies from one group of athletes to another. The research method was based on so-called discourse analysis. Two aspects were conspicuous: On the one hand, there is the concept of nationality and national pride attached to having a representative among the elite group of international athletes. On the other hand, sports reporters tend to focus on heroism and achievement. Other conclusions include that coverage relating to individual sports appears to contain similar elements, although it varies in amount of coverage. Developments during the 60 year period under investigation show coverage becoming more exaggerated and hyperbolical. This research also shows that the coverage is controlled by an interaction between the media, the world of athletics and society in general. Íþróttir eru aðaláhugamál verulegs hluta íslensku þjóðarinnar, a.m.k. ef marka má umfjöllun um þær í fjölmiðlum. Þrátt fyrir smæð þjóðarinnar hefur íslenskt íþróttafólk staðið sig vel á stórmótum erlendis og jafnvel unnið til verðlauna. Í greininni er fjallað um niðurstöður greiningar á umfjöllun prentmiðla sl. sextíu ár um íslenskt afreksíþróttafólk. Markmið greiningarinnar var að komast að því hvað sé sameiginlegt í þessari orðræðu, hvernig orðræða prentmiðlanna hefur þróast og hvort hún sé breytileg eftir hópum íþróttafólks. Notað var verklag sem kallast orðræðugreining. Tvennt skar sig úr í niðurstöðum greiningarinnar: Annars vegar er það þjóðernið og það þjóðernisstolt sem fylgir því að eiga ...